Learning Shorof Science at Zainul Hasan Geggong Islamic University Probolinggo | Pembelajaran Ilmu Shorof di Universitas Islam Zainul Hasan Genggong Probolinggo - Muzammil, Ahmad (An-nahdloh : Journal of Arabic Teaching, 2024)
Shorof is a qoidah in Arabic which discusses the origin of a word. Zainul Hasan Islamic University as an Islamic boarding school-based university makes Arabic one of the priority materials. On the Unzah campus there are 3 institutions that both teach Arabic. These 3 institutions consist of the Arabic Language Education department, the Center for Foreign Language Studies program and the Center for Qur'an and Qiro'atul Polar Studies, each of which has a different strategy in learning Arabic language material. PBA applies learning about the theory and practice of teaching Arabic and there is a special discussion about shorof science in a comprehensive manner, the PSBA program focuses on guiding students to be able to speak foreign languages, especially Arabic by including shorof science content, PSQQ emphasizes learning maharah Qiro'ah by including material shorof science. Because there are differences in the benchmarks of the 3 institutions, this research was created to describe how shorof science is taught at the University.